Relationship between Background Characteristics and Housing Satisfaction of Iranian Homeowners in Kuala Lumpur, Malaysia - Husniyah Binti Abdul Rahim, Mohamad Fazli Sabri, Bahare Fallahi, Ahmad Hariza Hashim (Journal of Educational, Health and Community Psychology, 2015)
AbstractThis research evaluated the association between socio demographic characteristics and housing satisfaction of Iranian immigrantâs homeowners in Kuala Lumpur, Malaysia. Data was collected from 325 participants through self-administered questionnaire. Pearsonâs correlation analysis revealed monthly income of first income earner, total earned income earner, price of residential unit, number of bed room, time owners have been in Malaysia, had positive significant relationship with housing satisfaction of Iranian immigrants homeowners in the study region. Nevertheless, there was no significant association between age, number of bath room, number of dining room, number of living room, length of residence in current house, monthly income of second income earner, number of income earner, number of children, and size of household and housing satisfaction of the immigrant ownersâ households. Analysis of variance (ANOVA) indicated that housing satisfaction differed between level of education, level of income, and level of price of residential unit. Independent t-test shown that there was significant difference between gender and housing satisfaction of the participants. These associations indicate that those who are females, higher income, higher education, higher residential unit with more room are more satisfied. It is recommended planners and policy makers should prominence on development of housing conditions of immigrantâs households to increase their housing satisfaction.Keywords: background characteristic, housing satisfaction, housing, immigrantâs homeownerâs households